Representatives of Chinese Society as Power Holders in the Images of Chinese Cinema - Musalitina, Evgenia A. (Journal of History Culture and Art Research, 2019)
The study considers the visualization of representatives of Chinese society as power holders in modern Chinese cinema. Cinema has been chosen as the source of research since it visually displays the processes taking place in society. As a result of an analysis of ten films of Chinese directors, the author identifies certain types of heroes who, to one degree or another, are endowed with power in modern Chinese society. Seven groups of power holders have been distinguished and characterized: members of the Triad mafia, police officers, officials, business representatives, the media, teachers, men as heads of families. A comprehensive study of these images is carried out, which includes an analysis of professional activity, social status, age criteria, visual and behavioral characteristics. The emphasis is placed on the complex relationship between the police and the mafia in the cinema: in addition to the traditional confrontation, the cinema presents a new version of the development of relations between the representatives of these groups - a mutually beneficial symbiosis. Still preserved in modern society traditional attitude the teacher and the head of the family as a source of power is shown. The images of business representatives as power-holders are revealed in the cinema through the opposition “material and moral”. There are relatively few images of direct holders of power – government officials in modern cinema. This fact can be explained by existing censorship in China.